Utilization of social media Instagram as A Promotional Media of Total Music Band - Permadi, Rizky; Muttaqien, Muhammad (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The development of communication is now not only carried out conventionally, but instead utilizes the internet as a more modern communication medium. One of the modern communications is using social media. Social media Instagram is the most used platforms where it places more emphasis on visual aspects such as sharing photos and videos. As a media communication, Instagram also provides other benefits, namely as a means of promotion. With a broad and unlimited audience reach, Instagram is used as a platform for product or service providers to engage with potential customers. One of the service providers that utilizes Instagram as a promotional medium is Total Musik Band. Total Musik is a band from Pringsewu Regency, Lampung with koplo genre. The purpose of this research is to find out how the use of Instagram as a means of promoting Total Musik Band. The method is used descriptive qualitative. The results of this study state that the Owner of Total Musik has received various positive impacts, including being better known by the people of Pringsewu Regency, not only that Total Musik has also received various offers from outside the Pringsewu district, such as in the Kalianda area (South Lampung), Metro, etc. Totak Musik also consistently uploads pamphlets with themes such as "Morning Ambyar", "Novembergoyang", "Desemberdendang" etc., so as to give viewers a visual and persuasive impression, the information also easier to understand. Total Musik now also has a loyal audience, this can be seen from the activity of the audience who came directly when Total Musik performed, where the audience created Instagram stories and then tagged the Total Musik Instagram account. As a form of appreciation, the Total Musik admin will repost all the stories tagged by the audience.